2011
DOI: 10.1088/0951-7715/24/10/003
|View full text |Cite
|
Sign up to set email alerts
|

Differentiability of fractal curves

Abstract: While self-similar sets have no tangents at any single point, self-affine curves can be smooth. We consider plane self-affine curves without double points and with two pieces. There is an open subset of parameter space for which the curve is differentiable at all points except for a countable set. For a parameter set of codimension one, the curve is continuously differentiable. However, there are no twice differentiable self-affine curves in the plane, except for parabolic arcs.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 12 publications
0
33
0
Order By: Relevance
“…See Section 13.5. (7) Recall that a Salem measure is a measure whose Fourier transform decays as fast as its Hausdorff dimension allows, see Section 14.1. We prove that a class of measures, which includes the natural measure on fractal percolation, are Salem measures when their dimension is ≤ 2 (and this is sharp), adding to the relatively small number of known examples of Salem measures.…”
mentioning
confidence: 99%
“…See Section 13.5. (7) Recall that a Salem measure is a measure whose Fourier transform decays as fast as its Hausdorff dimension allows, see Section 14.1. We prove that a class of measures, which includes the natural measure on fractal percolation, are Salem measures when their dimension is ≤ 2 (and this is sharp), adding to the relatively small number of known examples of Salem measures.…”
mentioning
confidence: 99%
“…, where c = c(n) > 0 is the constant from Lemma 2.4 (1). Together with the definition of A i this implies…”
Section: Dimension Of General Measures On Large Conesmentioning
confidence: 74%
“…(1) Bandt and Kravchenko showed that there are plenty of C 1 planar self-affine curves (i.e. self-affine sets that are C 1 planar curves); see [1,Theorem 2]. Furthermore, in [1,Theorem 3(ii)], they showed that parabolic arcs and straight line segments are the only simple C 2 planar self-affine curves.…”
Section: Self-affine Sets and Analytic Curvesmentioning
confidence: 99%
“…self-affine sets that are C 1 planar curves); see [1,Theorem 2]. Furthermore, in [1,Theorem 3(ii)], they showed that parabolic arcs and straight line segments are the only simple C 2 planar self-affine curves. This result also follows from Theorem A by a simple modification.…”
Section: Self-affine Sets and Analytic Curvesmentioning
confidence: 99%